Profiles of Occupational Therapy Students: A Cluster Analysis - Gry Mørk; Astrid Gramstad; Linda Stigen; Susanne Grødem Johnson; Tore Bonsaksen (MDPI AG, 2024)
While studies have examined predictors of study performance in various student groups, cluster analytic studies identify groups of students with similar characteristics. The purpose of this study was to explore relevant clusters of occupational therapy students and examine profile differences between participants in different clusters. A total of 177 first-year students from six occupational therapy programs in Norway participated in this study. Data on age, gender, study approaches, study effort, and study performance were collected. A two-step cluster analysis was conducted. Three clusters were identified. Cluster 1, the high-strategic high-performing students, comprised the successful students, mostly females, who invested much effort and used productive approaches to studying. Cluster 2, the high-surface average-performing students, consisted of less successful female students, who used poor study strategies and made little effort. Cluster 3, the low-strategic low-performing students, comprised the least successful students, who were all male, with study efforts and study strategies in the middle range. Overall, this study suggests that occupational therapy students can be classified into clusters based on a combination of measures. To enhance student learning and performance, educators should pay particular attention to male students and to students investing little effort and using poor study strategies.